2016
DOI: 10.1097/mph.0000000000000644
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Benefits of Bronchoalveolar Lavage and Lung Biopsy in the Management of Pulmonary Infiltrates in Children With Leukemia

Abstract: Background Children with leukemia are at risk of developing life threatening opportunistic pulmonary infections. The role of bronchoalveolar lavage (BAL) and lung biopsy (BX) in the management of these patients is controversial. In this study, we evaluate the yield and safety of BAL and BX in children with leukemia. Procedure We reviewed the records of all children with leukemia who underwent either BAL or BX between 1997 and 2007 at the St Jude Children’s Research Hospital. Results A total of 64 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…At St. Jude, patients with suspected PCP or with unexplained respiratory illness refractory to standard therapy typically undergo bronchoalveolar lavage to identify the presence of pneumocystis. During the study period, PCR gradually replaced immunofluorescence as the predominant test of PCP (21). Potential PCP cases were identified by the review of patient EMRs, ICD-9 codes (136.3), pharmacy and pathology records, and death summaries.…”
Section: Methodsmentioning
confidence: 99%
“…At St. Jude, patients with suspected PCP or with unexplained respiratory illness refractory to standard therapy typically undergo bronchoalveolar lavage to identify the presence of pneumocystis. During the study period, PCR gradually replaced immunofluorescence as the predominant test of PCP (21). Potential PCP cases were identified by the review of patient EMRs, ICD-9 codes (136.3), pharmacy and pathology records, and death summaries.…”
Section: Methodsmentioning
confidence: 99%
“…Antimicrobial coverage was changed in more than 83% of patients. Approximately 38% of patients who underwent BAL had complications, the most common of which was hypoxia ( 38 ). Prior studies report changes in antimicrobial management after BAL ( 37 39 ) but won’t comment on prognosis and survival except for three studies in which positive and negative BAL results prompted antimicrobial changes ( 1 , 40 ) but failed to show improvement in survival ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Which procedure gives the most helpful diagnostic information with the lowest complication rate remains to be answered. Many studies have compared both procedures in immunocompromised children but found no consensus on the superiority of one procedure ( 30 , 50 ). In a study that compared BAL to lung biopsy in a pediatric cohort post-HCT, the diagnostic yield of BAL was 40% compared to 94% with lung biopsy.…”
Section: Bal Versus Lung Biopsymentioning
confidence: 99%